Determination of Cost Savings and Energy Efficiency in Solar-Powered Water Pump Systems for Aquaponic Operation - LAU, XENA LENNIA; Asmawi, Rosli Bin; Zamri Noranai (Research Progress in Mechanical and Manufacturing Engineering, 2026)
Solar-powered water pump systems (SPWPS) allow a sustainable practice for aquaponic operations that combines aquaculture and hydroponics, relies heavily on efficient water circulation, which is typically powered by conventional energy sources. This study focuses on the installation of solar panels to power the water pumps and evaluates the cost savings compared to conventional energy sources while assessing energy efficiency in maintaining circulation of water. A Nutrient Film Technique (NFT) aquaponics system was designed and fabricated, using a 12V 9W polycrystalline solar panel with a DC submersible water pump capable of a maximum flow rate of 240 liters per hour. Performance testing was methodologically conducted under different weather conditions, along with a comparative analysis of operational costs between solar-powered and conventional-powered systems. The study identified the solar energy system not only reduced operational costs but also improved energy efficiency compared to conventional-powered system. The initial investment cost in solar technology is higher but it balanced by the cost savings on electricity bills and the environmental impact, as the used of renewable energy also contributed to a reduction of greenhouse gas emission. The used of solar-powered system displayed high energy efficiency in efficiently converting the solar energy to electrical power to maintain the water circulation that needed in aquaponic operations. The availability of sunlight and efficiency of component was found to be key factors that affecting system reliability. This approach is giving benefits for small-scale farmers and communities that particularly in rural areas where accessibility to electricity may be limited.